Rendimentos materiais e simbólicos do diploma de licenciatura em língua inglesa: estudo sobre egressos do curso de Letras da UFMG - Débora Fernandes de Miranda (2015)
The bachelor´s degree in English teaching is part of a context of relative devaluation of school titles and discredit of the teaching career. Besides, the English language as a school subject tends to be undervalued in regular schools. However, the major in English has the characteristic of certifying the mastery of a language, something that represents high distinctive value in the market of symbolic goods. Therefore, what can one expect from a BA in English if, on the one hand, it certifies valuable knowledge, but, on the other hand, it prepares professionals to work in a field where language teaching seems to be devalued, which is the school field? To address this question, this thesis investigated the material and symbolic returns on the bachelor´s degree in English teaching for former students of the Faculty of Letters of UFMG. To do so, the research was conducted in two stages: in the first one, we interviewed eleven directors and coordinators of public schools, private schools, and language institutes in Belo Horizonte, with the aim of drawing an approximate scenario of the main labor field of the students. In the second part, we interviewed twelve former students of the English major program of the Faculty of Letters of UFMG to investigate the social, cultural and economic impacts of the diploma on their lives. Through the analysis of their family, school, and professional backgrounds, we identified three groups with distinct returns on the diploma: to one group, the diploma expresses the fulfillment of a preference; to another group, it means upward social mobility; to a third group, it represents frustration. The results suggest that the returns on the diploma relate to the social and school profile of the individuals, their trajectories in the course, their personal and professional goals, and to the distinctive value represented by the mastery of a foreign language and the acquisition of cultural capital of an international character.